2018
DOI: 10.3390/ma11081428
|View full text |Cite
|
Sign up to set email alerts
|

Almond Shell as a Microporous Carbon Source for Sustainable Cathodes in Lithium–Sulfur Batteries

Abstract: A microporous carbon derived from biomass (almond shells) and activated with phosphoric acid was analysed as a cathodic matrix in Li–S batteries. By studying the parameters of the carbonization process of this biomass residue, certain conditions were determined to obtain a high surface area of carbon (967 m2 g−1) and high porosity (0.49 cm3 g−1). This carbon was capable of accommodating up to 60% by weight of sulfur, infiltrated by the disulphide method. The C–S composite released an initial specific capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…The N 2 adsorptioni sothermc urve at 77 Ki ss hown in Figure 2a; when sublimated sulfur is loaded into the pore channel of NUS-6, the BET surface area decreases from the initial 736 to 10 m 2 g À1 ,a nd the pore volume was also significantly reduced (from 0.27 to 0.026 cm 3 g À1 ), which indicates that most of the pores are occupied by sulfur.I na ddition, as shown in Figure 2b,t he pore size distribution diagram shows that NUS-6 is am icroporouss tructure, which is conducive to improving the cycle stability of lithium-sulfur batteries. [28,29] To explore the actual sulfur contenti nt he pores,t he S@NUS-6 was analyzed by thermogravimetry.D ue to the sublimation of sulfur,t he thermogravimetric curve shows that there is as ignificant weightl oss between 160 8Ca nd 260 8C, [30] and the weight loss accountsf or about 68 %o ft he total weight ( Figure S3). In order to exclude the influence of anion sulfonica cid group on lithium-sulfur batteries, [31,32] the high-resolution XPS spectra of NUS-6 and S@NUS-6 were tested, and the XPS spectrao fe le-mentsH fo fNUS-6 and S@NUS-6 are shown in Figure 2c.T he area ratio of the two peaks with binding energy of 17.23 eV and 18.8 eV is 4:3, which is the characteristicp eak of typical Hf 4f 7/2 and Hf 4f 5/2 .I na ddition, when sulfur was injected into the NUS-6 pore channel, the peak positiono fH f4fd id not change significantly.I nt he spectrum of S2 p, the corresponding characteristic peaks at 163.16 eV and 164.41 eV correspond to the orbit of S2 p 3/2 and S2 p 1/2 ,r espectively( FigureS4).…”
mentioning
confidence: 99%
“…The N 2 adsorptioni sothermc urve at 77 Ki ss hown in Figure 2a; when sublimated sulfur is loaded into the pore channel of NUS-6, the BET surface area decreases from the initial 736 to 10 m 2 g À1 ,a nd the pore volume was also significantly reduced (from 0.27 to 0.026 cm 3 g À1 ), which indicates that most of the pores are occupied by sulfur.I na ddition, as shown in Figure 2b,t he pore size distribution diagram shows that NUS-6 is am icroporouss tructure, which is conducive to improving the cycle stability of lithium-sulfur batteries. [28,29] To explore the actual sulfur contenti nt he pores,t he S@NUS-6 was analyzed by thermogravimetry.D ue to the sublimation of sulfur,t he thermogravimetric curve shows that there is as ignificant weightl oss between 160 8Ca nd 260 8C, [30] and the weight loss accountsf or about 68 %o ft he total weight ( Figure S3). In order to exclude the influence of anion sulfonica cid group on lithium-sulfur batteries, [31,32] the high-resolution XPS spectra of NUS-6 and S@NUS-6 were tested, and the XPS spectrao fe le-mentsH fo fNUS-6 and S@NUS-6 are shown in Figure 2c.T he area ratio of the two peaks with binding energy of 17.23 eV and 18.8 eV is 4:3, which is the characteristicp eak of typical Hf 4f 7/2 and Hf 4f 5/2 .I na ddition, when sulfur was injected into the NUS-6 pore channel, the peak positiono fH f4fd id not change significantly.I nt he spectrum of S2 p, the corresponding characteristic peaks at 163.16 eV and 164.41 eV correspond to the orbit of S2 p 3/2 and S2 p 1/2 ,r espectively( FigureS4).…”
mentioning
confidence: 99%
“…This trend was confirmed by Zhang et al [243], who reported values of around 600 mAh/g when using a microporous biochar. Similarly, Benitez et al [244] reported the use of microporous biochar as a cathodic material for a lithium-sulfur battery with a specific capacity of 915 mAh/g and a current density of 100 mA/g. Chen et al [245] showed that nitrogen doping could enhance hierarchical porous biochar activity derived from the pyrolysis of derived pomegranate residues at 700 • C of up to 550 mAh/g.…”
Section: Biochar Used For Batteries Productionmentioning
confidence: 97%
“…Similarly, all kinds of biowaste have been carbonized and used as host materials in the cathodes of lithium–sulfur, lithium–selenium, or lithium–oxygen batteries. Within recent years, for example, carbons made from waste materials such as fruit stones or peels, algae, nutshells, soybean hulls, grain waste, other plant waste, saw dust, and lignin have been described in this regard.…”
Section: Electrodesmentioning
confidence: 99%